Blockchain‐enabled secure crowdsensing for trackside infrastructure information collection and validation in railway signalling data preparation. Issue 1 (10th May 2021) - Muniandi, Ganesan
Abstract: Rail operators around the world are adopting advanced control systems for railway signalling and train protection to improve their safety performance. In these re‐signalling projects, the information about the already installed signals, point machines, track circuits etc. along the trackside infrastructure is essential for the configuration of advanced signalling equipment. The conventional information collection method which is based on unmanned aerial vehicles, helicopters etc. has the access limitations in terrains such as tunnels, hilly regions, river bridges, dense forests etc. To overcome these challenges, this paper proposes the railway vehicular crowdsensing method in which one group of trains participates in this information collection and another group of trains confirms the validity of the collected information. For information exchange between the trains and centralized server, this study chooses the permissioned blockchain‐based information transaction mechanism to ensure the trustworthiness. Furthermore, the railway markup language‐based blockchain databases are included for information immutability, crowd information integration, and the automatic execution of data preparation signalling rules. Finally, the case studies are carried out to analyse the adequacy of the proposed combination of crowdsensing based secure trackside infrastructure information collection and validation, permissioned blockchain‐enabled information transaction and blockchain databases in the proposed signalling data preparation process.